Utilization of serology for the diagnosis of suspected Lyme borreliosis in Denmark: Survey of patients seen in general practice - Dessau, Ram B (BioMed Central, 2010)
BACKGROUND: Serological testing for Lyme borreliosis (LB) is frequently requested by general practitioners for patients with a wide variety of symptoms. METHODS: A survey was performed in order to characterize test utilization and clinical features of patients investigated for serum antibodies to Borrelia burgdorferi sensu lato. During one calendar year a questionnaire was sent to the general practitioners who had ordered LB serology from patients in three Danish counties (population 1.5 million inhabitants). Testing was done with a commercial ELISA assay with purified flagella antigen from a Danish strain of B. afzelii. RESULTS: A total of 4,664 patients were tested. The IgM and IgG seropositivity rates were 9.2% and 3.3%, respectively. Questionnaires from 2,643 (57%) patients were available for analysis. Erythema migrans (EM) was suspected in 38% of patients, Lyme arthritis/disseminated disease in 23% and early neuroborreliosis in 13%. Age 0-15 years and suspected EM were significant predictors of IgM seropositivity, whereas suspected acrodermatitis was a predictor of IgG seropositivity. LB was suspected in 646 patients with arthritis, but only 2.3% were IgG seropositive. This is comparable to the level of seropositivity in the background population indicating that Lyme arthritis is a rare entity in Denmark, and the low pretest probability should alert general practitioners to the possibility of false positive LB serology. Significant predictors for treating the patient were a reported tick bite and suspected EM. CONCLUSIONS: A detailed description of the utilization of serology for Lyme borreliosis with rates of seropositivity according to clinical symptoms is presented. Low rates of seropositivity in certain patient groups indicate a low pretest probability and there is a notable risk of false positive results. 38% of all patients tested were suspected of EM, although this is not a recommended indication due to a low sensitivity of serological testing.